Psychological wellness of health-care professionals during the coronavirus disease-2019 pandemic - Lakshmi Ranganathan; Nagarajan Ramakrishnan (Apollo Medicine)
Background: The outbreak of the coronavirus disease-2019 (COVID-19) has been a major health crisis and is associated with psychological distress, specifically in health-care workers (HCW). Our study aimed to assess psychological wellness and sleep disturbances among HCW during the COVID pandemic and also to determine if the symptoms differed in those who were involved in caring for COVID patients in comparison with those who were not. Methods: This observational, cross-sectional survey was conducted during April–May 2020 at two facilities of a tertiary care hospital in Chennai, India, that provided care for COVID-19 patients. HCWs working in the critical care units and designated COVID units were included. A survey questionnaire comprising three components ‒ demographics, psychological wellness, and sleep ‒ was administered by email to participants. Results: The survey was sent to 230 HCW, and 190 completed it (response rate – 82.6%); the mean age was 29.7 ± 9.7 years; males/females–70 [36.8%]/120 [63.2%]). The overall mean depression score was 16.6 ± 4.4, indicating moderately severe depression. The overall mean anxiety score was 10.1 ± 3.4, indicating moderate anxiety. About 35.3% of the participants got <6 h of sleep, 56.3% reported inadequate sleep, and 52.6% reported disturbed sleep‒wake cycle. “Risk of getting infected” was the most important impacting factor (57.9%), followed by “disturbed work-life balance” (40.5%) and “uncertainty of outcomes” (24.2%). There were no differences in the depression, anxiety scores, or sleep quotients between the COVID treating and nontreating groups. Conclusion: Health-care professionals report high rates of symptoms of depression, anxiety, and sleep disturbances during the COVID-19 pandemic, irrespective of their involvement in caring for infected patients.